2002
DOI: 10.1094/cchem.2002.79.3.458
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Structural Characteristics of Flours and Starches from Waxy and Nonwaxy Wheats

Abstract: A waxy spring wheat (Triticum aestivum L.) genotype was fractionated into flour and starch by roller and wet‐milling, respectively. The resultant flour and starch were evaluated for end‐use properties and compared with their counterparts from hard and soft wheats and with commercial waxy and nonwaxy corn (Zea mays L.) starches. The waxy wheat flour had exceptionally high levels of water absorption and peak viscosity compared with hard or soft wheat flour. The flour formed an intermediate‐strength dough that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
62
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 23 publications
14
62
0
Order By: Relevance
“…1c). Unlike potato starch, diffraction peaks were not as prominent with either CTAB.With the addition of surfactants, potato starch and wheat flour produced a V-type diffraction pattern, while native wheat starch and flour had a typical A-type pattern similar to results reported by Abdel-Aal et al, 32 .…”
Section: Sem Analysis Proceduressupporting
confidence: 85%
“…1c). Unlike potato starch, diffraction peaks were not as prominent with either CTAB.With the addition of surfactants, potato starch and wheat flour produced a V-type diffraction pattern, while native wheat starch and flour had a typical A-type pattern similar to results reported by Abdel-Aal et al, 32 .…”
Section: Sem Analysis Proceduressupporting
confidence: 85%
“…Silver nitrate (AgNO 3 ) can be used as an alpha-amylase inhibitor to verify the presence of endogenous amylase activity in flours and characterise the pasting properties of flour without enzyme interference (Abdel-Aal, Hucl, Chibbar, Han, & Demeke, 2002;Collado & Corke, 1999). In this study, all three waxy rice flours showed an increase in peak viscosity in the presence of AgNO 3 (Fig.…”
Section: Effects Of Treatments On Pasting Property Of Three Waxy Ricementioning
confidence: 68%
“…High pasting viscosity, breakdown, and swelling power are desirable functional properties for the textural quality of white salted noodles (5)(6)(7)(8)(9). These starch characteristics are largely determined by amylose content of starch (10)(11)(12). Amylose content of wheat starch is controlled by granule bound starch synthase (GBSS).…”
Section: Introductionmentioning
confidence: 99%